Hubungan Persepsi dan Minat Mahasiswa PGSD Terhadap Pemanfaatan Permainan Tradisional Sebagai Sumber Belajar di Sekolah Dasar - Syamsul Darmawan; Ade Fitriani HR; Rahmat Darmawan (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2026)
Traditional games have the potential to serve as culture-based learning resources that support contextual learning in elementary schools. However, their utilization in the learning process remains relatively low, including among Elementary School Teacher Education (PGSD) students as prospective teachers. This study aims to analyze the relationship between PGSD students’ perceptions and interests toward the use of traditional games as learning resources in elementary schools. This study employed a quantitative approach with a correlational design. Data were collected through questionnaires and analyzed using descriptive statistics and Pearson Product Moment correlation tests. The results showed that PGSD students had positive perceptions and high interest in the use of traditional games as learning resources. In addition, there was a positive and significant relationship between students’ perceptions and interests. These findings indicate that more positive perceptions toward traditional games are associated with higher interest in implementing them in elementary school learning. This study confirms that traditional games have the potential to be developed as active, contextual, and culture-based learning media.